STATUS MUTU AIR SUMUR GALI DAN PENGENDALIANNYA DI PEMUKIMAN PIR2 ARSO KABUPATEN KEEROM - Suhartawan, Bambang -; Iriyanto, Santje; Alfons, Alfred B.; Daawia, Daawia (DINAMIS, 2022)
Utilizing hygienic and sanitary water is absolutely necessary to avoid unwanted negative impacts. This research was conducted in PIR 2, Arso, Keerom Regency from August to October 2022. This research aims to determine the quality status of dug well water by using the pollution index method with 18 (eighteen) water pollution parameters namely: physical parameters (turbidity, color, TDS, temperature, taste and smell), chemical parameters (pH, iron, fluoride, hardness, manganese, nitrate, nitrite, cyanide, detergents and total pesticides) as well as biological parameters (total Coliform and Escherichia coli). The samples in this research were taken from four sample points (research stations), namely station 1 (line 1), station 2 (line 2), station 3 (line 3) and station 4 (line 4). The results showed that the water quality status of dug wells at stations 2 and 3 obtained a pollution index of 10.28 and 12.72 respectively and classified as heavily polluted, while at stations 1 and 4 the pollution index was 2.38 and 4.80 respectively and both stations were classified as lightly polluted. Water parameters that did not qualify water quality standards were turbidity, iron content and Escherichia coli. A suitable water management plan to fulfill the quality standard requirements was the well water must be filtered using zeolite media, sand, palm fiber and activated carbon (coconut shell charcoal) and added a little chlorine (chlorine) or alum to the reservoir before filtration.